Drawing with YouTube in Early Childhood: Cognitive Outcomes and Pedagogical Implications - Alam, Samsul; Yusny, Rahmat (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study explores the role of drawing with YouTube in enhancing cognitive development among early childhood learners. Using an instrumental qualitative case study in one public kindergarten (TK Negeri Pembina Semarang) comprising eight classes with 138 children aged 4–6 years and nine teachers, data were collected through classroom observations, teacher interviews, and analysis of children’s drawings. The findings indicate that guided drawing with YouTube tutorials improved children’s observational accuracy (e.g., identifying geometric forms), stimulated collaborative creativity (e.g., divergent colour use), and fostered problem-solving skills (e.g., adaptive material substitution). These results suggest that drawing with YouTube serves as an effective visual learning medium supporting early cognitive and creative growth through multimodal engagement. In the global discourse on digital childhoods, this study provides evidence that structured digital use can transform screen media from passive consumption into active cognitive engagement. It contributes to worldwide discussions on multimodal literacy and digital creativity as essential competencies for young learners. However, the study is limited by its single-site context and lack of longitudinal analysis. Future research should include broader samples, cross-cultural comparisons, and quantitative validation to deepen understanding of the cognitive impacts of digitally mediated drawing activities. Practically, the findings highlight the pedagogical value of integrating short, guided YouTube videos with open-ended questioning to enhance visual literacy, reflective thinking, and creative autonomy in early childhood classrooms.